2006
DOI: 10.1111/j.1348-0421.2006.tb03768.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination with Linear DNA to Insert Antigenic Protein in the Flagellin: Improvement of the Th1 Immune Response

Abstract: Bacterial flagellin is a surface protein with numerous advantages for the presentation of exogenous peptides. However, the production of recombinant bacteria and the expression of fusion proteins is laborious and time consuming. Here, we present a simple way to produce modified bacteria. Partially deleted, non-functional, chromosomal flagellin gene (fliC ) was changed using homologous recombination by a functional linear fliC gene in which we introduced an exogenous oligonucleotide encoding for the peptide of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(45 reference statements)
0
7
1
Order By: Relevance
“…+ T cells is crucial for the induction of an effective CTL response and protective antitumor immunity (23,47). Further confirmation that pFlg liposomes can be used to elicit Ag-specific responses was provided by our demonstration that vaccination of C57BL/6 mice with 9Flg-and 42Flg-OVA liposome induced Agspecific T cell priming, as assessed by the ability to induce increased Ag-specific cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…+ T cells is crucial for the induction of an effective CTL response and protective antitumor immunity (23,47). Further confirmation that pFlg liposomes can be used to elicit Ag-specific responses was provided by our demonstration that vaccination of C57BL/6 mice with 9Flg-and 42Flg-OVA liposome induced Agspecific T cell priming, as assessed by the ability to induce increased Ag-specific cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with this, a number of studies showed that flagellin has adjuvant-like properties (17,18) Vaccination with recombinant flagellin-Ag fusions induced potent T and B cell responses, including Ag-specific CD8 + T cell and Ab responses to model Ags (19,20), as well as to a number of disease-relevant Ags (21)(22)(23), including influenza M2e Ag (24), Plasmodium vivax merozoite surface protein-1 (25), and Mycobacterium tuberculosis Ag p27 (26). The responses induced were often much greater than those induced by vaccination of the Ag emulsified in CFA (20)(21)(22)(23)(24)(25)(26). Also, the linking of flagellin to Ag is essential to induce detectable Ab responses, because a simple mixing of the two is not sufficient (20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The antibody response, systemic (IgG) or secreted (IgA), against flagellin was dependent on the route of immunization [17] and finally, immunization of mice with a fusion protein containing a flagellin-enhanced green protein was capable of stimulating antigen presenting cells and thus develop a specific T-cell response [18]. We previously used this strategy and obtained a good Th1 response against two different bacterial antigens [19,20]. …”
Section: Introductionmentioning
confidence: 99%